DRUG PRESCRIBING PATTERN IN INTENSIVE CARE UNIT (ICU) IN A TERTIARY CARE TEACHING HOSPITAL IN CENTRAL INDIA - DR.RAJENDRA GUPTA (International Journal of Pharma and Bio Sciences, 2015)
To study the drug prescribing pattern in Intensive Care Unit (ICU) in a tertiary care teaching hospital in central India. It was a retrospective and observational study,conducted during the period of September 2014 to February 2015. Data was obtained through the prescription record of 146 patients admitted in the Medical ICUfrom Medical Record Department of the hospital.Data was analyzed for- Most common causes for admission to ICU, male and female admission ratio, average number of drugs prescribed per prescription, Outcome of the patients, percentage usage of various antimicrobial groups. Most common cause for admission in ICU was found to be Myocardial Infarction (MI) followedby angina. In all diseases number of male patients was found to be more than female patients. Average no of drugs perpatients was found to be 7.82, Improvement was seen in 87.23% patients and mortality was seen in 2.23% patients.While condition remained same in 10.54% patients at the time of discharge. Cephalosporins were the most commonlyprescribed antimicrobial group (65.33%) followed by aminoglycosides.